Answer:
A, C & D
Step-by-step explanation:
A) 1 + 3x = -x + 4 {subtract 1}
1 + 3x -1 = -x + 4 - 1
3x = -x + 3 {add x}
3x + x = -x + 3 + x
4x = 3 {Divide by 4}
4x/x = 3/4
x = 3/4
C) 1 + 3x = -x +4 {Add x}
1+ 3x + x = - x +4 + x
1 + 4x = 4 {subtract 1}
4x = 4 - 1
4x = 3 {Divide by 4}
D) 1 + 3x = -x + 4 { Subtract 3x}
1 = -x + 4 -3x
1 = -4x + 4 Subtract 4}
1 - 4 = -4x
-3 = -4x {Divide by -4}
-3/-4 = x
x = 3/4
x = 3/4
Answer:
<h2>Make the points more Appealing</h2>
Step-by-step explanation:
B. The expression has 4 factors and 0 constants.
The factors separately are:
4
a
b
(c+3)
Factors are numbers or expressions that produce a givens product.
Looking at the expression we can rewrite it as:
4 x a x b x (c+3)
The overall value with be the product of all the factors.
Hey there! I'm happy to help!
Let's have the adult tickets be a and the children tickets be c.
a=2c (twice as many adult tickets as child tickets)
5a+2c=700 (dollar value of each ticket)
Have a wonderful day! I hope that the helps! :D
Answer: 10 cats
Step-by-step explanation:
3/2
15/x
3*5=15
2*5=10
3/2=15/10
Download the aappp called Socratic